A calculus problem by Viki Zeta

Calculus Level 5

n = 1 1 n 2 n 1 \large \sum_{n=1}^\infty ~ \dfrac{1}{n^2- n - 1}

The series above can be expressed as π tan ( A B π ) A \dfrac{\pi \tan\left(\frac{\sqrt A}B \pi \right)}{\sqrt A} for positive integers A A and B B , find A + B A+B .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

S = n = 1 1 n 2 n 1 = n = 1 1 ( n 1 + 5 2 ) ( n 1 5 2 ) = 1 5 n = 1 ( 1 n 1 + 5 2 1 n 1 5 2 ) = 1 5 n = 1 ( 1 n 1 n + 5 1 2 1 n + 1 n 5 + 1 2 ) = 1 5 ( ψ ( 5 1 2 + 1 ) + γ ψ ( 1 5 + 1 2 ) γ ) See Notes. = 1 5 ( ψ ( 5 + 1 2 ) ψ ( 1 5 + 1 2 ) ) = 1 5 ( π cot ( 5 + 1 2 π ) ) See Notes. = π tan ( 5 2 π ) 5 \begin{aligned} S & = \sum_{n=1}^\infty \frac 1{n^2-n-1} \\ & = \sum_{n=1}^\infty \frac 1{\left(n - \frac {1+\sqrt 5}2\right)\left(n - \frac {1-\sqrt 5}2\right)} \\ & = \frac 1{\sqrt 5} \sum_{n=1}^\infty \left({\color{#3D99F6}\frac 1{n - \frac {1+\sqrt 5}2}} - {\color{#D61F06}\frac 1{n - \frac {1-\sqrt 5}2}} \right) \\ & = \frac 1{\sqrt 5} \sum_{n=1}^\infty \left(\frac 1n - {\color{#D61F06}\frac 1{n + \frac {\sqrt 5-1}2}} - \frac 1n + {\color{#3D99F6}\frac 1{n - \frac {\sqrt 5+1}2}} \right) \\ & = \frac 1{\sqrt 5} \left({\color{#D61F06}\psi \left(\frac {\sqrt 5-1}2+1\right) + \gamma} - {\color{#3D99F6}\psi \left(1-\frac {\sqrt 5+1}2 \right) - \gamma} \right) & \small {\color{#3D99F6}\text{See Notes.}} \\ & = \frac 1{\sqrt 5} \left(\psi \left(\frac {\sqrt 5+1}2\right) - \psi \left(1-\frac {\sqrt 5+1}2 \right) \right) \\ & = \frac 1{\sqrt 5} \left(- \pi \cot \left(\frac {\sqrt 5+1}2 \pi \right) \right) & \small {\color{#3D99F6}\text{See Notes.}} \\ & = \frac {\pi \tan \left(\frac {\sqrt 5}2 \pi \right)}{\sqrt 5} \end{aligned}

A + B = 5 + 2 = 7 \implies A+B = 5+2 = \boxed{7}


Notes: ψ ( ) \psi(\cdot) is the digamma function .

  • Theorem: ψ ( s + 1 ) = γ + k = 1 ( 1 k 1 k + s ) \displaystyle \psi(s+1)=-\gamma+\sum_{k=1}^\infty \left(\dfrac{1}{k}-\dfrac{1}{k+s}\right) , where γ \gamma is the Euler-Mascheroni constant .
  • Theorem: ψ ( 1 z ) ψ ( z ) = π cot π z \psi(1-z) - \psi(z) = \pi \cot \pi z

Fascinating.....

yohenba soibam - 4 years, 6 months ago

Fantastic solution sir!!

A Former Brilliant Member - 3 years, 2 months ago

Log in to reply

Glad that you like it.

Chew-Seong Cheong - 3 years, 2 months ago

Great solution, upvoted!

André Hucek - 3 years, 1 month ago

Another solution:

Note that cos ( π x ) = n 1 ( 1 4 x 2 ( 2 n 1 ) 2 ) π tan ( π x ) = 8 x n 1 1 ( 2 n 1 ) 2 4 x 2 \cos(\pi x)=\prod_{n\ge 1}\left(1-\frac{4x^2}{(2n-1)^2}\right)\\\implies \pi \tan(\pi x)=8x\sum_{n\ge 1}\frac{1}{(2n-1)^2-4x^2} by taking log \log followed by differentiating. Using 4 x 2 1 = 4 x = 5 2 4x^2-1=4\implies x=\frac{\sqrt{5}}{2} , we find n 1 1 n 2 n 1 = π tan ( π 5 2 ) 5 \sum_{n\ge 1}\frac{1}{n^2-n-1}=\frac{\pi \tan(\pi \frac{\sqrt{5}}{2})}{\sqrt{5}} implying the answer to be 5 + 2 = 7 5+2=\boxed{7} .

Ah, Weierstrass factorization theorem . One of my favorite introductory complex analysis theorems.

Pi Han Goh - 4 years, 7 months ago

Cool!... xD...

Viki Zeta - 4 years, 7 months ago

wonderful idea! thanks :)

Rohith M.Athreya - 4 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...